Assessment of the Population of Medium and Small Towns of Europe in the Last Quarter of the 19th Century in the Works by Professor Alexander Georg Supan - Руденко, Валерій Петрович; Білоус, Вікторія (Pedagogical University of Krakow Polish Geographical Society – Industrial Geography Commission, 2023)
This article highlights the results of an assessment of population dynamics in medium and small towns in Europe in the years 1875, 1880, 1890, and 1904. These data were presented by Alexander Georg Supan (1847–1920) in his “Lehrbuch der Geographie nach den Principien der neueren Wissenschaft für österreichische Mittelschulen und verwandte Lehranstalten sowie zum Selbstunterrichte” (“Textbook of Geography for Austrian Middle Schools and Related Institutions, as Well as Self-Instruction”), published in the second (1875), fourth (1880), seventh (1890), and eleventh (1904) editions. Particular emphasis is placed on the fact that over the last quarter of the 19th century, the number of medium-populated towns exceeded a fifth of all European cities while small towns comprised a tenth. The article presents the population dynamics of 131 medium-sized towns in Europe in 1875, 1880, 1890, and 1904. It also establishes that medium towns were more typical of Austria-Hungary and Germany than other European countries.
Keywords: Alexander Georg Supan; medium and small towns of Europe